Sowiecki dzikus, cuchnący dorsz i Muza – Władysława Chodasiewicza widzenie Petersburga - Brzykcy, Jolanta (Studia Rossica Posnaniensia, 2024)
The aim of this article is to analyze and interpret Vladislav Khodasevich’s poem Petersburg (Петербург, 1925), in which the poet evokes the image of the city during the war communism period from the distance of emigration. The poet presents the city in many dimensions: as a place of struggle for physical survival in an era of crisis caused by the Russian Civil War; as a space where high culture clashed with the barbarism of Bolshevism; and in an autobiographical key – as a time in which his own creative forces flourished. The cityscape is based on a series of antinomies: past – present, tradition – innovation, spirituality – materiality, sacrum – profanum, the real world – the surreal world, the culture of old Russia – the primitivism of new times. This allows us to look at the poem simultaneously from several perspectives: historical-literary (cultural life in St. Petersburg during the Civil War), biographical (the poet’s stay in the city in the years 1920–1922), intertextual (assignment of the poem to the Petersburg text) and metatextual/self-referential (Khodasevich’s aesthetic views).